About the ontological-genetic method in Philosophy - Nicolas Tertulian (Universidade Federal de Santa Catarina, 2010)
The starting point of the author is the observation that Lukács' statute in the contemporary philosophical scenery is far from being elucidated. A ponderous silence surrounds, after many decades, his two works of synthesis: The Aesthetics and The Ontology of the social being. On the other hand, now it me- ans to show that Lukács has been the first to undertake a genealogy of the multiple activities of the conscience and their objectifications (economy, rights, politics and its institutions, art or philosophy) from the dialectical tension between subjectivity and objectivity. That is to say, there is in the last thought of the Hungarian philosopher an "ontological-genetic" method, since it is attached to show the progressive stratification of the subject (for example: utilitarian activity, hedonistic activity and aesthetic activity), indicating the transitions and mediations, until the circumscription of each specificity in function of the role that it fills in social life phenomenology.